Procurement regimens to reduce ischemia reperfusion injury of vascular grafts - Abele-Ohl, S.; Heim, Christian; Eckl, Stefanie; Weyand, Michael; Stamminger, Thomas; Ensminger, S. M. (European Surgical Research, 2012)
Background: Ischemia reperfusion injury is an important nonimmunological factor contributing to the development of chronic rejection. The aim of this study was to compare different cell culture media in terms of vascular lesion formation after ischemia reperfusion injury. Methods: BALB/c aortic grafts were incubated in different cell media (endothelial cell growth, ECG, RPMI-1640 and Waymouth/Ham's F12) for various time spans (5, 6.5 and 8.5 h) at 37°C and implanted into syngeneic BALB/c recipients. On day 30 after implantation, histology, immunofluorescence and morphometric measurements were performed. Results: A total of 36 transplants were performed for this study with an overall survival rate of 72.2%. The most frequent complication was thrombosis of the aortic graft (n = 9) and there was one late death due to other courses. All the recipients with vascular grafts incubated in the ECG medium survived and showed no signs of intimal proliferation independent of the time of ischemia. Aortic grafts incubated in the RPMI medium resulted in a reduced recipient survival rate of 66.7% and grafts incubated in the Waymouth medium showed only a 50% survival by day 30. Analysis of the vascular morphology revealed moderate amounts of intimal proliferation within two aortic grafts in this group. CD31 staining revealed superior endothelial cell integrity after incubation with the ECG medium. Conclusions: Data from the current study suggest that under optimized conditions vascular grafts can be safely kept in tissue culture up to 8.5 h without significant ischemic damage. Differences in vascular integrity and animal survival depended mostly on the respective tissue culture medium used for the storage of the vessel. © 2012 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Endothelial cell integrity; Ischemia reperfusion injury; Tissue culture medium; Transplant arteriosclerosis; Vascular grafts